2014
DOI: 10.1186/1748-717x-9-154
|View full text |Cite
|
Sign up to set email alerts
|

A cohort analysis to identify eligible patients for intraoperative radiotherapy (IORT) of early breast cancer

Abstract: BackgroundSince the results from the randomized TARGIT A trial were published, intraoperative radiotherapy (IORT) is used more often. IORT can be provided as accelerated partial breast irradiation (APBI) or as a boost. The definition of suitable patients for IORT as APBI differs between different national societies (e.g. ESTRO and ASTRO) and different inclusion criteria of trials and so does the eligibility of patients. This analysis identifies eligible patients for IORT according to available consensus statem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
19
0
3
Order By: Relevance
“…Acute radiation pneumonitis and chronic radiation fibrosis represent common consequences of radiation exposure in the setting of treatment of various cancers (22), including non-small cell lung cancer, small cell lung cancer (23), breast cancer (24), esophageal cancer (25), mediastinal tumors (26), and head and neck tumors (27). Although the underlying biology of radiation-induced injury to the lung is becoming increasingly known, few actionable targets exist for the purposes of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute radiation pneumonitis and chronic radiation fibrosis represent common consequences of radiation exposure in the setting of treatment of various cancers (22), including non-small cell lung cancer, small cell lung cancer (23), breast cancer (24), esophageal cancer (25), mediastinal tumors (26), and head and neck tumors (27). Although the underlying biology of radiation-induced injury to the lung is becoming increasingly known, few actionable targets exist for the purposes of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…E, HBECs were transfected with scramble and silencer-miR-15b and incubated for 24 h. Cells were then treated with IR (4 Gy) and incubated for another 24 h. Total RNA was extracted, cDNA was synthesized, and qRT-PCR was performed with miR-15b primer (*, p Ͻ 0.001). 24 h after transfection, cells were exposed to IR and incubated for another 24 h. Total proteins were extracted, and the presence of Wip1, total and phosphorylated ATM, total and phosphorylated Chek1, MDM2, phospho-p53, ␥-H2AX, Rad51, and cleaved PARP was assessed by Western blot analysis (Fig. 6A).…”
Section: Wip1 (Ppm1d) Is a Target Of Mir-15b/16-2-mentioning
confidence: 99%
“…Vaidya JS et al have reported in TARGIT A, a phase III clinical trial that for patients with early breast cancer <2 cm the tumor local control rate of IORT is not inferior to external beam radiotherapy after breast conserving surgery; external beam radiotherapy should be considered for patients with tumor of 2 -3 cm or with poorer prognostic factors [6]. Sperk E et al have reported that patient selection for IORT should be restrictive when provided as accelerated partial breast irradiation (APBI) [4].…”
Section: Discussionmentioning
confidence: 99%
“…Dedicated IORT device commercially available includes Mobetron ® MeV electron beam system [1] (Intra Op Medical Corporation, California, USA), NOVAC™ 7 system (New Radiant Technology SpA, Italy) and the INTRABEAM ® 50 kV X-ray device (Carl Zeiss Medical Company, Germany). Since the results from the randomized TARGIT A trial were published, IORT has been applied for locally advanced or recurrent rectal cancer [2], superficial cutaneous malignancies [3] and as full dose partial breast irradiation (PBI) or as a boost after whole-breast radiatherapy (WBI) in early stage breast cancer [4] [5]. Vaidya J.S.…”
Section: Introductionmentioning
confidence: 99%
“…This development was supported by novel insights into breast cancer tumor biology. The concept of accelerated partial breast irradiation (APBI) was rigorously tested in several large-scale clinical studies [4,5,6,7], and has now entered clinical guidelines (for a summary, see [8,9]). The current article reviews some of the underlying biological concepts, summarizes the results of the practice-changing clinical trials and tries to give an overview on the current status of ongoing additional clinical studies.…”
Section: Introductionmentioning
confidence: 99%